The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1590/fst.116222
|View full text |Cite
|
Sign up to set email alerts
|

Effect of packaging method and storage temperature on the sensory quality and lipid stability of fresh snakehead fish (Channa striata) fillets

Abstract: The objective of the present study was to investigate the effect of packaging methods (i.e., air-packaging and vacuum-packaging) and storage temperatures (i.e., chilled temperature of 3 ± 1.0 °C and superchilled temperature of -2.5 ± 0.5 °C) on the sensory quality and lipid stability of fresh snakehead fish fillets. The results indicated that vacuum packaging and superchilled storage significantly improved the quality of fresh snakehead fillets, resulting in lower free fatty acids (FFA), hydroperoxide (PV), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In a similar study, the lipid content in mussel meat decreased from 43.5 to 33.6% after 15 days of cold storage (Bejaoui et al, 2021). Storage conditions (temperature and time) had a greater effect on the final lipid content than the packaging method (Nguyen et al, 2023).…”
Section: The Lipid Changing Of Flesh Meat From Tra Catfish During 15 ...mentioning
confidence: 79%
“…In a similar study, the lipid content in mussel meat decreased from 43.5 to 33.6% after 15 days of cold storage (Bejaoui et al, 2021). Storage conditions (temperature and time) had a greater effect on the final lipid content than the packaging method (Nguyen et al, 2023).…”
Section: The Lipid Changing Of Flesh Meat From Tra Catfish During 15 ...mentioning
confidence: 79%
“…Yang et al [ 104 ] showed that acid value increased significantly during smoking and boiling in Procambarus clarkii . Increased in acid index during boiling may be linked to heating water that catalyzes the hydrolysis of ester bonds of triglycerides and phospholipids by triglyceride lipase and releases free fatty acids in oil [ 105 ]. High content of free fatty acid (FFA) in oil leads to the formation of off-flavor as a result of rancidity of oil [ 1 ] .…”
Section: Resultsmentioning
confidence: 99%